'Career and Money Aside, What's the Point of University?' A Comparison of Students' Non‐economic Entry Motives in Three European Countries. (16th May 2016) - Bartram, Brendan
Abstract: This paper explores students' non‐economic motives for attending university. Drawing on the results of a tri‐national survey involving online questionnaires and email interviews with education students at English, German and Portuguese universities, it compares and discusses the extent to which the participants are motivated by a number of extrinsic and intrinsic factors. In contrast to certain other studies, the findings reveal a strong consensus across all three settings in relation to certain motivational elements—strong intrinsic desires for self‐improvement and low motivations driven by social pressures or seeing university as a default option. More pronounced national differences emerge, however, regarding motives to contribute to society and the appeal of the social dimension of university life. The paper interprets the similarities and differences revealed and considers a number of conclusions.